Persepsi Mahasiswa Terhadap Kompetensi Dosen Jurusan Pendidikan IPS Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako - Hamid, Abdul (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2023)
This research aims to know the perception of students on the competence of education faculty in IPS, very important to study and know about the existence of the competency of lecturers according to their expertise, the results, and the achievements of students who do not look prominent and analyze the factors such as the competency of lecturers grouped into 4 competencies, namely; Competency, professional competence, personality competence, and social competence. This is the essence of the issue raised in this study. Then, it was analyzed using a descriptive percentage analysis and data analysis. Based on the results of data analysis, it can be concluded that the student perception gained calculation of the lecturer competency attitude is: 22% answered always, 63% responded often, 13% reacted rarely and 2% answered never. From the results, the student perception attitude towards the competence of the Faculty of IPS, most of the answer often with the highest answer number is 68% so the perception attitude of students to the competence of the Faculty of IPS is categorized well.